2020
DOI: 10.3390/v12121404
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1C env and gag Variation in the Cerebrospinal Fluid and Plasma of Patients with HIV-Associated Cryptococcal Meningitis in Botswana

Abstract: HIV-1 compartmentalization in reservoir sites remains a barrier to complete HIV eradication. It is unclear whether there is variation in HIV-1 env and gag between cerebrospinal fluid (CSF) and plasma of individuals with HIV-associated cryptococcal meningitis (CM). We compared HIV-1 env characteristics and the gag cytotoxic T-lymphocyte (CTL) escape mutations from CSF and plasma samples. Employing population-based Sanger sequencing, we sequenced HIV-1 env from CSF of 25 patients and plasma of 26 patients. For g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…The few CTL escape mutations in Gag that differed in frequency between compartments did not coincide with compartmentalisation. Consistent with these results, previous studies have shown that CTL escape is similar between different anatomical locations where the virus is compartmentalised ( Miller et al, 2019 ; Kelentse et al, 2020 ). It is possible that the immune environment is not sufficiently different between the compartments studied to drive significant differences in Gag CTL escape mutations between compartments, and the conserved nature of Gag when compared to Env may also be partly responsible.…”
Section: Discussionsupporting
confidence: 89%
“…The few CTL escape mutations in Gag that differed in frequency between compartments did not coincide with compartmentalisation. Consistent with these results, previous studies have shown that CTL escape is similar between different anatomical locations where the virus is compartmentalised ( Miller et al, 2019 ; Kelentse et al, 2020 ). It is possible that the immune environment is not sufficiently different between the compartments studied to drive significant differences in Gag CTL escape mutations between compartments, and the conserved nature of Gag when compared to Env may also be partly responsible.…”
Section: Discussionsupporting
confidence: 89%
“…The immune response plays a key role in the control of virus infection. Several studies have demonstrated that virus mutations allowing escape from the host immune response generally lead to the resistance to antiviral therapy and progression to disease ( 61 , 62 ). For example, in HBV genome, amino acid substitutions in the S region producing the mutated surface antigen may induce immune escape, such as G145R ( 63 ), Q129H ( 64 ) and I195M ( 65 ), etc.…”
Section: Construction and Contentsmentioning
confidence: 99%